Acute Thrombotic Occlusion of the Left Brachial Artery After Intra-Arterial Administration of Amiodarone. Issue 4 (April 2016) - Witkowski, Marco; Mochmann, Hans-Christian; Rauch, Ursula; Knie, Wulf; Landmesser, Ulf; Skurk, Carsten
Abstract : Objective: To report a case of intra-arterial amiodarone injection in a hemodynamically unstable patient leading to acute vessel occlusion and a subsequent compartment syndrome. Design: Case report. Setting: Prehospital setting, emergency department and ICU of a university hospital. Patient: A 58-year-old woman presenting with a ventricular tachycardia of 190 beats/min was administered amiodarone through an accidently placed arterial access in the left cubital fossa. Quickly, the woman developed clinical signs of an acute arterial occlusion. Interventions: Immediate left brachial artery angiography with subsequent thrombectomy was performed. Measurements and Main Results: A thrombotic occlusion at the injection side was found, which was immediately recanalized by thrombus aspiration. In addition to anticoagulation and an adenosine diphosphate-antagonist an adjunct therapy with vasodilators and gpIIb/IIIa inhibitors was given and repetitive duplex sonography confirmed arterial flow. However, despite restoration of blood flow the patient developed a severe compartment syndrome of the arm and had to receive multistep surgical interventions. Conclusions: This is the first report of an acute thrombotic vessel occlusion leading to a compartment syndrome upon accidental intra-arterial injection of amiodarone in an emergency setting. In the hemodynamically unstable patient healthcare providers should be aware of arterial miscanulation and its consequences. Upon intra-arterial injection, a direct antithrombotic and vasodilative therapy should be administered via the initially misplaced arterial access, which may include a gpIIb/IIIa inhibitor. Abstract : Supplemental Digital Content is available in the text.